Tanzania : Accounting and Auditing - World Bank (Washington, DC, 2012)
This report provides an assessment of accounting and auditing practices within the context of the Tanzania institutional framework, to ensure the quality of corporate financial reporting. Various weaknesses and encouraging advancements were identified in the course of the review. Company legislation is outdated. A revised Act provides for modernized requirements but has shortcomings and is still not effective. Some laws specify particular accounting requirements that do not align with International Financial Reporting Standards/International Accounting Standards (IFRS/IAS). Parastatals lack a single statutory financial reporting act and there is no law, or regulatory body monitoring financial reporting by pension funds. On a positive side, the Auditors and Accountants Act has facilitated the development of an enabling environment for strong accounting practices, and the mandatory appointment of professional accountants for entities meeting thresholds. Another positive development was the adoption of IFRS/IAS and International Standards on Auditing (ISA) in 2004. However, full compliance is not yet readily achieved and national ethical requirements for auditors have not kept up to date with international developments. While the National Board of Accountants and Auditors (NBAA) has made a significant contribution to accountancy development over the past decade, the professional education however, is not yet in line with International Educational Standards, and neither is the NBAA able to function effectively either as a regulator, or, a professional accountancy body. The policy recommendations provided in this report focus on improving the statutory framework, strengthening enforcement mechanisms, upgrading professional education and training, and enhancing capacity of regulatory and professional bodies. Establishing an independent oversight body is a major recommendation. The oversight body would be responsible for adoption, monitoring, and enforcement of IFRS/IAS - based and ISA-based accounting and auditing practices of public interest entities. In addition, stakeholders should agree on criteria to clarify which entities should be eligible to use the standards of the International Accounting Standards Board for small- and medium-size enterprises, when available.